Pig Farmers' Perceptions of Economic Incentives to Control Salmonella Prevalence at Herd Level - Olsen, Jakob Vesterlund; Christensen, Tove; Jensen, Jørgen Dejgaard (Frontiers in Veterinary Science, 2021)
This paper investigates how perceived costs and benefits of Salmonella control among Danish pig farmers affect the farmers' choice of action toward reducing the prevalence of Salmonella in their herds. Based on data from an online questionnaire involving 163 Danish pig farmers, we find a considerable uncertainty among pig farmers about the perceived effects of the Salmonella reducing actions. The results indicate large variations in the perceived costs of implementing different types of Salmonella reducing actions (management-, hygiene- and feed-related). For some cases, farmers associate net benefits and positive productivity effects with implementation of the actions while studies by the industry indicate net costs to the farmers. Differences among farmers support the idea of an outcome-based Salmonella penalty scheme but the large uncertainties about costs and effects of actions toward Salmonella control might hamper the effectiveness of such a penalty scheme as a regulatory instrument to affect farmer behavior.